2013
DOI: 10.1016/j.bmc.2013.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a promising fluorine-18 labelled radiopharmaceutical for in vivo imaging of fatty acid amide hydrolase

Abstract: Fatty acid amide hydrolase (FAAH), the enzyme responsible for terminating signaling by the endocannabinoid anandamide, plays an important role in the endocannabinoid system, and FAAH inhibitors are attractive drugs for pain, addiction, and neurological disorders. The synthesis, radiosynthesis, and evaluation, in vitro and ex vivo in rat, of an 18F-radiotracer designed to image FAAH using positron emission tomography (PET) is described. Fluorine-18 labelled 3-(4,5-dihydrooxazol-2-yl)phenyl (5-fluoropentyl)carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 46 publications
4
42
0
Order By: Relevance
“…It was found that a linear N -alkyl substituent leads to increased potency over cyclic isomers and that the presence of a dihydrooxazole confers faster and greater brain uptake with lower nonspecific binding. These insights lead directly to the design of two fluorine-18 labeled FAAH radiotracers: [ 18 F]DOPP 75,76 and [ 18 F]FCHC. 77 Both show greater brain uptake in vivo and sensitivity to FAAH activity in vitro than [ 11 C]CURB.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…It was found that a linear N -alkyl substituent leads to increased potency over cyclic isomers and that the presence of a dihydrooxazole confers faster and greater brain uptake with lower nonspecific binding. These insights lead directly to the design of two fluorine-18 labeled FAAH radiotracers: [ 18 F]DOPP 75,76 and [ 18 F]FCHC. 77 Both show greater brain uptake in vivo and sensitivity to FAAH activity in vitro than [ 11 C]CURB.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…The compound was administered by intraperitoneal injection in rats 30 min prior to the administration of [ 18 F]-3-(4,5-dihydrooxazol-2-yl)phenyl (5-fluoropentyl)carbamate ( 18 F-DOPP) an irreversible and brain penetrant 18 F-labelled FAAH inhibitor. [63] It was postulated that pretreatment with 3 would prevent the interaction of 18 F-DOPP with FAAH. [64] However, administration of 3 at two different dosages had no effect on brain labeling with 18 F-DOPP, which is suggestive of limited penetration.…”
Section: Approaches To the Design Of Multi-target Faah/cox Inhibitorsmentioning
confidence: 99%
“…To our knowledge, two of those radiotracers have been evaluated in humans, the irreversible radioligand [ 11 C]CURB, which has been validated in modeling studies [18], and [ 11 C]MK-3168, a reversible radioligand prepared at Merck [20]. While clinical translation is planned for two additional FAAH radiotracers [17,19], it is noteworthy that there have been no reported attempts to prepare MAGL radiotracer for imaging studies.…”
Section: Introductionmentioning
confidence: 99%